Increased Ability to Face Disaster Threats for Children with Special Needs in Inclusion Elementary Schools at Yogyakarta City - Komalasari, Mahilda Dea (Proceeding International Conference on Science and Engineering, 2019)
The potential for many disasters in the city of Yogyakarta needs to be addressed with a training to improve the ability to face disaster threats, especially for children with special needs. This training aims to increased ability to face disaster threats for children with special needs in inclusion elementary schools at Yogyakarta City. The capacity building training to face the threat of disaster was carried out by lecture, question and answer, and demonstration methods. This training took place at SDN Karanganyar and SDN Minggiran. Both of these elementary schools are inclusion in the city of Yogyakarta. Based on observations at SDN Karanganyar and SDN Minggiran, it is necessary to conduct training to improve the ability to face disaster threats to improve the ability to face disaster threats because there were students with special needs who did not understand how to protect and save themselves in the event of a disaster. Therefore, The goals of this community partnership program are teacher and students with special needs in SDN Karanganyar and SDN Minggiran, and implemented from February 2018 to October 2018. Through training to improve the ability to face disaster threats, it is expected to improve the ability of students with special needs in facing disaster threats.